Effectiveness of Combination of Gotu Kola (Centella Asiatica (L.) Urban) and Aloe Vera Herb Extracts as a Natural Disinfectant - Delladari Mayefis; Sri Hainil; Andi Bunga Dahlia; Ghalib Syukrillah Syaputra; Nurlia Oktaviyanti (Jurnal EduHealth, 2023)
Disinfectants are products used to kill microorganisms inside or on the surface of an inanimate object. One of the plants used to kill microorganisms is Gotu Kola (Centella Asiatica (L.) Urban) and Aloe Vera. This study aims to determine the effectiveness and at what concentration the combination of Gotu Kola and Aloe Vera herb extracts can be used as a natural disinfectant. The research was conducted using an experimental method by counting the number of colonies before and after disinfection on a dinner plate. The results showed that the calculation of the percentage reduction in the number of germs on the dinner plate after disinfection using Aloe vera obtained the results of 44.6% at a concentration of 25%, 89.2% at a concentration of 50% and 95.3% at a concentration of 100%. While the percentage reduction in the number of germs on the dinner plate after disinfection using a combination of herb extracts of Gotu Kola and Aloe Vera with a ratio of 1: 2 obtained results of 73.3% at a concentration of 50% and 93% at a concentration of 100%. The combination of Gotu Kola and Aloe Vera extracts can be used as a natural disinfectant at a ratio of 1: 2.